Simulation study on surface deformation of shallow buried coal seam mining in a gully area - Wang, Xin; Cai, Lailiang; Zhang, Bingjie; Wu, Jingdong; Zhu, Quanshun; Cui, Zhoufeng (Frontiers in Earth Science, 2023)
Coal mining subsidence leads to frequent surface ecological and environmental problems. Due to the unique topographic conditions within gully areas, the deformation and damage characteristics, along with the evolution laws of the surface, have been difficult to analyze. To explore the surface movement and deformation law of shallow-buried coal seam mining in a gully area, this study designed a three-dimensional similar-material simulation test simulating the complete movement and deformation of the ground surface under real terrain conditions and proposed a complete data acquisition and processing scheme. Combined with the numerical simulation analysis, we utilized this scheme to analyze the dynamic influence law of coal seam mining in a gully area on the distribution of ground surface stress and displacement as well as on the dynamic characteristics of the ground surface damage. The results show that the existence of gully topography affects the stress distribution of the ground surface and the raw rock of the coal seams underneath and that there exists a stress concentration in the gully area of the ground surface. Furthermore, the mining activities of the coal seams lead to an increase in the degree of stress concentration in the gully area of the ground surface, and the slopes enter into the process of energy accumulation and sudden release, which makes the region prone to the occurrence of geological disasters such as landslides and collapses. In addition, the surface movement and deformation in the gully area are more intense, exceeding the plain area, and the surface movement is affected by the spatial location relationship between the mining area and the slope body, causing the center of the mining area to show obvious eccentricity characteristics. The results of this study provide a reference basis for the safe mining of coal mines in gully topography.